BEHAVIORISTIC LEARNING THEORY - Nurfadillah Nurfadillah; Andi Abd. Muis; Al Khaisyurahman; Elsa Sapitri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to find out behavioristic learning theory according to experts, the characteristics of behavioristic learning theory and also find out the advantages and disadvantages of behavioristic theory. This research is a literature review which aims to look for theories that are used as reference sources and are used as reference research libraries (Library Research), where in the process of collecting data by searching for relevant journals and from research that has been carried out previously using keywords from the article title. The results of this research found that behaviorist learning theory is oriented towards